Tree-Dwelling Ants: Contrasting Two Brazilian Cerrado Plant Species without Extrafloral Nectaries - Jonas Maravalhas; Jacques H. C. Delabie; Rafael G. Macedo; Helena C. Morais (Psyche: A Journal of Entomology)
Ants dominate vegetation stratum, exploiting resources like extrafloral nectaries (EFNs) and insect honeydew. These interactions are frequent in Brazilian cerrado and are well known, but few studies compare ant fauna and explored resources between plant species. We surveyed two cerrado plants without EFNs, Roupala montana (found on preserved environments of our study area) and Solanum lycocarpum (disturbed ones). Ants were collected and identified, and resources on each plant noted. Ant frequency and richness were higher on R. montana (67%; 35 spp) than S. lycocarpum (52%; 26), the occurrence of the common ant species varied between them, and similarity was low. Resources were explored mainly by Camponotus crassus and consisted of scale insects, aphids, and floral nectaries on R. montana and two treehopper species on S. lycocarpum. Ants have a high diversity on cerrado plants, exploring liquid and prey-based resources that vary in time and space and affect their presence on plants.